A Multi-Year Scenario-Based Transmission Expansion Planning Model Incorporating Available Transfer Capability - Tohid Akbari; Saeed Zolfaghari Moghaddam (AUT Journal of Electrical Engineering)
This paper presents a multi-year scenario-based methodology for transmission expansion planning (TEP) in order to enhance the available transfer capability (ATC). The ATC is an important factor for all players of electricity market who participate in power transaction activities and can support the competition and nondiscriminatory access to transmission lines among all market participants. The transmission expansion planning studies deal with many uncertainties, such as system load uncertainties that are considered in this paper. The Latin hypercube sampling (LHS) method has been applied for generating different scenarios related to the load uncertainty. The objective function in the TEP model is to minimize the sum of investment costs (IC) and the expected operation costs (OC). Both ATC and TEP models are represented based on AC power flow constraints which are more accurate compared with the widely-used DC approach. In this respect, the nonlinear terms in power flow equations are linearized in order to obtain the efficient solutions by existing commercial solvers that can guarantee the achievement to the global optimal solution using branch and bound technique. The proposed model is applied to the IEEE 24-bus Reliability Test System and the results obtained show the efficiency, tractability and applicability of the proposed model.